Per Vintilă - Marianne Mesnil; Radu Răutu; Cristina Papa; Zoltán Rostás; David A. Kideckel; Raluca Nahorniac; Cătălin A. Stoica; Ellen Hertz; Bogdan Iancu; Monica Stroe; Ger Duijzings; Maria V. Grecu; et al. (Anuac, 2020)
In memory of Vintilă Mihăilescu (1951-2020).